Analisis Ketentuan Fiskal terhadap Laporan Keuangan Komersial untuk Menentukan Besarnya PPh Terhutang Studi Kasus pada Yayasan Pendidikan âYPKTHâ - Pamungkas, H. Bambang; De Poere, Daniel Benyamin; Ridwan, Amalia (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2009)
The objective of this research is to analyze fiscal stipulation toward commercial financial report of foundation, if it met justice principle and other principles that form the background of circular publication and rules about the foundation. The method used at this research is comparative method, trying to compare commercial financial report, that is financial report according to principle and accounting stipulation that be in effect (PSAK) with fiscal financial report according to principle and taxation stipulation (UU No. 17, 2000). From this reconciliation, it will be yielded fiscal profit or revenue that will be a basis to count income tax that must be paid in one tax year. Keywords: Foundation Financial Report, Company Fee Taxpayer, Fiscal Correction